Mikroenkapsulasi Asam Mefenamat Menggunakan Polimer Kitosan dan Natrium Alginat dengan Metode Gelasi Ionik: Microencapsulation of Mefenamic Acid Microcapsules With Chitosan and Sodium Alginate as Polymer Using Ionic Gelation Method - Mardikasari, Sandra Aulia; Suryani; Akib, Nur Illiyyin; Indahyani, Rezki (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2020)
Mefenamic acid belongs to a class of the Non-steroidal Anti-Inflammatory drugs that work as an analgesic. But mefenamic acid can cause gastrointestinal disorders, has unpleasant odors and tastes and sensitive to the influence of light and temperature. Microencapsulation technology is a technique where the active substance is coated by a thin layer so that the active substance is protected from environmental influences. The aim of this research was to formulate and characterize mefenamic acid in the form of microencapsulation using ionic gelation methods. Preparation was done by comparing 3 variations of concentrations of sodium alginate polymers. Success parameters include the entrapment efficiency, particle shape, particle size distribution, and dissolution test. The results showed that the entrapment efficiency respectively 98,69%, 96,38% and 93,98%, with spherical shape, and particle size that fulfilled the microencapsulation size range of 1,268 Î¼m, 1,343 Î¼m and 1.386 Î¼m and the release of the active ingredients in an acidic medium of pH 1.2 was 8.811 mg/L, 6.751 mg/L and 5.965 mg/L, also on a base medium of pH 7.4 was 79.908 mg/L, 63.394 mg/L and 40,312 mg/L. So that microencapsulation of mefenamic acid can be prepared with polymer chitosan and sodium alginate using the ionic gelation method.